(untitled) (The Pakistan Development Review, 1998)
This paper aims to explore Pakistan’s geo-economic options in the difficult situation that confronts following the easing of sanctions, which added acute balance of payments pressures to its existing ailments of near-stagnant exports, a lower growth trend than in preceding decades, an unattractive climate for foreign investment, and weak social indicators. The first question explored is whether Pakistan has any opportunity of participating in a regional trade grouping. It is argued that the only conceivable way of achieving this would involve the development of SAARC, which would demand a profound transformation of Indo-Pakistani relations (though one no more profound than that realised in Franco-German relations since the founding of what is now known as the European Union). One benefit of achieving deep integration through SAARC is that this would create the possibility of Pakistan developing a serious engineering industry far more rapidly than will otherwise happen. In the absence of deep integration in SAARC, it is argued that Pakistan’s best option would be a policy close to unilateral free trade, so as to place it in a position to take advantage of whatever the next generation of labour-intensive activities demanded by the world economy proves to be. Under either of those scenarios, the reestablishment of a dynamic industrial sector will require the maintenance of a competitive exchange rate, something that, it is argued, is not necessarily guaranteed by floating. The paper also discusses the role of inward direct investment in contributing to the export success of East Asia, and considers whether the expatriate Pakistani community might be capable of playing a role comparable to that played by the overseas Chinese in nurturing the Chinese export expansion of the last two decades. It is suggested that such a hope was set back by the extra-legal attempt to renegotiate power tariffs with the independent power producers in the course of 1998, and that Pakistan needs to become a country of laws rather than discretion if foreign investors, including expatriate Pakistanis, are ever to find the country an attractive export platform. While more inward direct investment would almost certainly be beneficial, the same is not true for inward financial investment, where too large an inflow can easily expose a country to very significant risks, as the East Asian crisis showed. In the long run, Pakistan needs to be prepared to repel excessive capital inflows if they materialise; but its immediate problem is still balance of payments pressure, and this seems to demand targeting a major and sustained improvement in the current account over the next several years.